Political parties' portrayal attempts in creating an image of Aceh's women politicians - Mardhiah, Ainol; Puspasari, Cindenia; Anismar, Anismar; Mulyadi, Mulyadi (Jurnal Studi Komunikasi, 2022)
This study aims to provide an overview of political imagery done by political parties for their female politicians. The constructivist paradigm with a descriptive qualitative approach is used in this study. The informants were the chairman of the DPC of the Democratic Party, the PPP Party, the PKB Party, the chairman of the PDI-P DPD, and female politicians from these parties. The data analysis technique used in this study was the Interactive Model Data Analysis method. The results show that the political parties establish a positive image of women politicians, including involving all women members of the political party in every activity carried out by the party, both in a formal party and non-formal activities within the community. In every activity in the community, political parties attempted to provide the public with an understanding of the importance of the presence of women in the political space, because women will understand women's needs and produce feminist policies. The political imagery was done through political communication media, interpersonal (face to face), groups, mainstream media, and modern media. Political image establishment attempted by political parties for female politicians still has not shown a promising direction. Therefore, political parties must form a positive image for female politicians of their parties. This should be done massively by utilising various media of political communication, involving all community groups, such as the Ulama, Academics, and Non-Governmental Organisations.